2022
DOI: 10.1038/s41388-022-02368-w
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of innate and adaptive immune regulation underlie poor oncologic outcomes associated with KRAS-TP53 co-alteration in pancreatic cancer

Abstract: Co-occurrent KRAS and TP53 mutations define a majority of patients with pancreatic ductal adenocarcinoma (PDAC) and define its pro-metastatic proclivity. Here, we demonstrate that KRAS-TP53 co-alteration is associated with worse survival compared with either KRAS-alone or TP53-alone altered PDAC in 245 patients with metastatic disease treated at a tertiary referral cancer center, and validate this observation in two independent molecularly annotated datasets.Compared with non-TP53 mutated KRAS-altered tumors, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…In this cohort, we did not have an adequate sample size to analyze the clinical outcome from wild-type KRAS with GATA6 amplification. It was previously shown that both KRAS and TP53 mutations are independently associated with poor prognosis [39], and our cohort with TP53 mutation co-harbored KRAS mutation at the same time. Therefore, it will be interesting to see the interaction between GATA6 amplification with KRAS activation.…”
Section: Discussionsupporting
confidence: 60%
“…In this cohort, we did not have an adequate sample size to analyze the clinical outcome from wild-type KRAS with GATA6 amplification. It was previously shown that both KRAS and TP53 mutations are independently associated with poor prognosis [39], and our cohort with TP53 mutation co-harbored KRAS mutation at the same time. Therefore, it will be interesting to see the interaction between GATA6 amplification with KRAS activation.…”
Section: Discussionsupporting
confidence: 60%
“…By contrast, TP53/KRAS co-mutated non-small cell lung cancer patients benefited from PD-L1 blockage in comparison to docetaxel, while KRAS -mutant patients without additional TP53 mutation did not [ 60 ]. A distinct immunoregulatory program was uncovered in TP53 / KRAS co-mutated pancreatic ductal adenocarcinoma [ 61 ]. In models of TP53mut triple-negative breast cancer restoration of TP53 activity sensitized for blockade of the PD-L1/PD1 axis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,20 This lack of concordance might be attributable to our substantially larger cohort size and/or the inherent heterogeneity of patients enrolled in this pragmatic “real world” study capturing data with wide geographic and clinicodemographic variability, which present novel insights into the genotype-immunophenotype chasm in YOPC. 47 Multiple pathways enriched in YOPC tumors converged upon regulation of the tumor immune microenvironment with various predicted effects. For instance, cytokine signaling, cancer pathways, and angiogenic signaling may restrict tumor immunity.…”
Section: Discussionmentioning
confidence: 99%